Stringency of environmental targets in animal agriculture: shedding light on policy with shadow prices - Huhtala, Anni; Marklund, Per-Olov (Oxford University Press, 2008)
We present a framework for deriving shadow prices for regulations on manure-spreading in animal agriculture and demonstrate that these prices can be used as indicators of the stringency of environmental regulation. We illustrate our approach with the case of water protection measures implemented in Finland to restrict the use of phosphorus on livestock farms. The estimated shadow price of the nutrient limit lies in the range 60 125 per kilogram of bioavailable phosphorus in manure, assuming that output reduction is the only option for decreasing the amount of manure in manure-dense areas. However, instead of cutting output, farms may be able to avoid these high abatement costs by more efficient input use or alternative abatement methods.
Keywords: Ma; Suomi; ympäristölainsäädäntö; kotieläintilat; karjanlanta; fosfori; ylituotanto; teknologia; hinnat; environment; regulations; phosphorus; surpluses; technology; prices; Finland; environmental regulation; technology choises; phosphorous surplus; manure; livestock farms